Wage rigidity or fiscal redistribution? The unemployment bias of time consistent redistributive policies - Etienne Lehmann (Institute for the Study of Labor (IZA), 2006)
Because of Time Inconsistency considerations, policymakers underestimate the drawbacks of wage rigidity as a redistributive tool. Consequently, they redistribute inefficiently income from high to low skilled workers. They typically implement too much wage rigidity whereas other means (in particular fiscal transfers) could achieve the same redistributive goal with less perverse effect on unemployment. Time inconsistency is more likely due to lack of credibility than to the short-term horizon of policymakers. Hence, policymaking processes should be reformed towards more transparent and binding agreements between government and social partners.
Keywords: D78; H2; J68; 330; unemployment; inequality; wage rigidity; time inconsistency